Rischio e post-sviluppo vesuviano: Un’antropologia della “catastrofe annunciata” - Gugg, Giovanni (Antropologia Pubblica, 2024)
The risk concept, meant as hierarchical historical and cultural product, is a social elaboration acquiring different meanings according to the context. Even though it is inevitably characterized by indeterminacy, it is, in its practical purposes, a vision of the future affecting the present time: therefore, following certain principles, it could be possible to avert, control, mitigate a future disaster. In this way, the emergency planning becomes a political outlook made up of laws, territorial delimitations, emergency drills, preparedness, resilience pedagogy. In such general picture, the case of Vesuvius volcano in Naples district stands out. In 2011 the scientific journal Nature defined it as «the Europe’s ticking time-bomb». The certainty of a future eruption together with the uncertainty about the time and way in which it will take place, make the effects of the “announced catastrophe” visible in the practices and policies that are currently carried out by local governments and communities. Contrary to what is repeated by a stereotype, the ethnographic data show how the inhabitants of the Vesuvius area, anything but indifferent to the volcano threat, have a various and differentiated approach to it. It is a valuable case study for anthropology to reflect upon the “prevention society”, the “risk culture” and the effects of a “development” ideology that led to an over-urbanization considered as the main vulnerability source, not only for a potential natural disaster.